The time-evolving epileptic brain network: concepts, definitions, accomplishments, perspectives - Bröhl, Timo; Rings, Thorsten; Pukropski, Jan; von Wrede, Randi; Lehnertz, Klaus (Frontiers in Network Physiology, 2024)
Epilepsy is now considered a network disease that affects the brain across multiple levels of spatial and temporal scales. The paradigm shift from an epileptic focus -a discrete cortical area from which seizures originate -to a widespread epileptic network -spanning lobes and hemispheres -considerably advanced our understanding of epilepsy and continues to influence both research and clinical treatment of this multi-faceted high-impact neurological disorder. The epileptic network, however, is not static but evolves in time which requires novel approaches for an in-depth characterization. In this review, we discuss conceptual basics of network theory and critically examine state-of-the-art recording techniques and analysis tools used to assess and characterize a time-evolving human epileptic brain network. We give an account on current shortcomings and highlight potential developments towards an improved clinical management of epilepsy.